SMALL AND MEDIUM ENTERPRISES: DYNAMICS AND SPECIFIC CRITERIA FOR THE OPERATION OF THE MARKET - Boris Morgoev (Вестник Северо-Кавказского федерального университета)
In an article in the cross-country aspect is considered sector of the Russian small business, revealed the typical structure of the SME sector in the Russian Federation, as well as the structure of the economic activities of SMEs, the institutional dynamics of SME sector development in the regional context, is a comparison of quantitative and qualitative criteria for the identification of small businesses that allows you to systematize trends and socio-economic functions of the SME sector in the Russian Federation.